UPAYA TAMAN MUDA IBU PAWIYATAN YOGYAKARTA DALAM MELESTARIKAN BUDAYA TRADISIONAL MELALUI KESENIAN KARAWITAN - arief, ardian; Lestari, Fahmi Sasanti (Program Studi Pendidikan Guru Sekolah Dasar Universitas Katolik Musi Charitas, 2019)
Efforts to preserve traditional culture in the implementation of musical art in class IV and class V students in Taman Muda (Elementary School) Ibu Pawiyatan Tamansiswa Yogyakarta were examined using qualitative methods. The data found in this regard are 1) teaching how to beat gamelan and singing Javanese songs according to the correct technique, teaching ethics in music, maintaining gamelan in a complete and orderly condition, and participating in cultural performances or musical competitions; 2) supporting factors for the implementation of musical art in Taman Muda Ibu Pawiyatan Tamansiswa namely adequate and adequate gamelan, competent musical teachers, high student enthusiasm and enthusiasm, musical learning activities carried out according to the schedule in each class, musical learning hours are sufficient, as well as facilities and infrastructure that support musical learning activities; 3) the inhibiting factors of the implementation of musical art in Taman Muda Ibu Pawiyatan Tamansiswa namely there are students with special needs who need extra guidance and a long process to be able to beat the gamelan according to the correct technique, there are students who are not concentrated when the teacher submits musical material because of conversation talking with his friend, and the teacher not from the musical field replaced the musical teacher who was unable to teach.